Understanding the effect of laser scan strategy on residual stress in selective laser melting through thermo-mechanical simulation - Parry, L.; Ashcroft, Ian; Wildman, Ricky D. (Elsevier, 2016)
Selective laser melting (SLM) is an attractive technology, enabling the manufacture of customised, complex metallic designs, with minimal wastage. However, uptake by industry is currently impeded by several technical barriers, such as the control of residual stress, which have a detrimental effect on the manufacturability and integrity of a component. Indirectly, these impose severe design restrictions and reduce the reliability of components, driving up costs. This paper uses a thermo-mechanical model to better understand the effect of laser scan strategy on the generation of residual stress in SLM. A complex interaction between transient thermal history and the build-up of residual stress has been observed in the two laser scan strategies investigated. The temperature gradient mechanism was discovered for the creation of residual stress. The greatest stress component was found to develop parallel to the scan vectors, creating an anisotropic stress distribution in the part. The stress distribution varied between laser scan strategies and the cause has been determined by observing the thermal history during scanning. Using this, proposals are suggested for designing laser scan strategies used in SLM.